2008
DOI: 10.1007/s11120-008-9329-7
|View full text |Cite
|
Sign up to set email alerts
|

The activities of PEP carboxylase and the C4 acid decarboxylases are little changed by drought stress in three C4 grasses of different subtypes

Abstract: The C4 photosynthetic pathway involves the assimilation of CO2 by phosphoenolpyruvate carboxylase (PEPC) and the subsequent decarboxylation of C4 acids. The enzymes of the CO2 concentrating mechanism could be affected under water deficit and limit C4 photosynthesis. Three different C4 grasses were submitted to gradually induced drought stress conditions: Paspalum dilatatum (NADP-malic enzyme, NADP-ME), Cynodon dactylon (NAD-malic enzyme, NAD-ME) and Zoysia japonica (PEP carboxykinase, PEPCK). Moderate leaf deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Significant PEP-CK activity in C 4 grasses and eudicots of the NADP-ME and NAD-ME subtypes has been previously reported (Walker et al , 1997; Wingler et al , 1999; Carmo-Silva et al , 2008; Muhaidat and McKown, 2013). These findings challenge the classical view of the C 4 subtypes, where a single decarboxylase dominates (Hatch, 1987; Furbank, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Significant PEP-CK activity in C 4 grasses and eudicots of the NADP-ME and NAD-ME subtypes has been previously reported (Walker et al , 1997; Wingler et al , 1999; Carmo-Silva et al , 2008; Muhaidat and McKown, 2013). These findings challenge the classical view of the C 4 subtypes, where a single decarboxylase dominates (Hatch, 1987; Furbank, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…5; Supplementary Table S4). Previous reports also demonstrated the crucial roles of PEPC genes in various stress responses and in hormone signaling transduction278910, which motivated us to perform expression profile analyses of GmPEPC genes under various abiotic stress and hormones treatments. The results showed that Al, cold, salt or PEG stress could alter the expression level of soybean PEPC genes and soybean PEPC activity (Figs 7 and 8).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, accumulating evidence has confirmed that a large number of PEPC genes are induced by abiotic and biotic stresses and play important roles in regulation of plant tolerance to stress267. For example, an up-regulated PEPC expression in response to salinity or drought stress has been well documented in C 3 , C 4 and CAM plants678910. Meanwhile, overexpression of PEPC gene in transgenic plants enhanced their tolerance to drought or salt stress11, whereas knockdown of PEPC leading to increased sensitivity to osmotic stress12.…”
mentioning
confidence: 98%
“…As a warm-season perennial grass, bermudagrass is widely used as turfgrass on sport fields, golf courses and home lawns. Drought stress is a world-wide problem, and different grass species may develop different strategies to tolerate, escape, or avoid drought stress condition [4], [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%